Association of Gestational Hypertension with Neonatal Cardiovascular Physiology: Gestational Hypertension with Neonatal Cardiovascular Physiology - Afridi, Sanodia; Khan, Imran; Mumtaz, Asfa; Bibi, Shabnam; Gul, Haji; Ahmad, Khalil (Pakistan Journal of Health Sciences, 2025)
Gestational hypertension (GH) is a common hypertensive disorder of pregnancy associated with increased maternal and neonatal risks. While its impact on maternal cardiovascular health is well-established, its effects on neonatal cardiovascular physiology remain insufficiently explored. Objective: To examine the association between GH severity and neonatal cardiovascular outcomes. Methods: A cross-sectional observational study was conducted at Health Net Hospital, Peshawar, including 150 mother-neonate pairs diagnosed with GH. Participants were categorized into mild, moderate, and severe GH groups per ACOG criteria. Neonatal cardiovascular parameters heart rate, blood pressure, pulmonary artery pressure, LVEF, and CHD, were assessed. One-way ANOVA and Chi-square tests analyzed group differences, while logistic regression identified independent predictors of NICU admission. Results: Of the 150 neonates, 34% required NICU admission, with all severe GH cases admitted (p<0.001, Cramer’s V=0.638). One-way ANOVA showed no significant differences in heart rate, blood pressure, or LVEF across GH groups (p>0.05), though LVEF showed a borderline trend (p=0.059). Logistic regression confirmed GH severity as an independent predictor of NICU admission (OR: 0.181, 95% CI: 0.097–0.339, p<0.001), while birth weight was non-significant (p=0.575). Conclusions: It was concluded that the severity of gestational hypertension is significantly associated with adverse neonatal cardiovascular outcomes, particularly NICU admission. GH severity independently predicted NICU requirement, emphasizing the need for close monitoring and early intervention in pregnancies complicated by moderate to severe GH.